IMPLEMENTASI METODE OUTDOOR LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA KELAS V SEKOLAH DASAR NEGERI 22 SULUR MEDAN DI DESA SUMBER HARAPAN TAHUN PELAJARAN 2024-2025 - Sarita Sarita; Rusiadi Rusiadi; Bayu Bayu (CV. ADIBA AISHA AMIRA, 2025)
This research aims to describe the planning, implementation, supporting and inhibiting factors of outdoor learning method in Islamic Religious Education (PAI) learning for fifth grade students at SDN 22 Sulur Medan. This study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results showed that teachers planned the learning carefully, including learning objectives, media, and outdoor learning locations. The implementation was carried out in three stages: introduction, core activities such as Hajj simulation, and evaluation. Supporting factors included students’ enthusiasm, adequate facilities, and school environment, while inhibiting factors included weather conditions, students’ moods, and external disturbances. This study concludes that outdoor learning effectively improves students’ motivation and understanding in PAI learning.